The Role of Citizenship Education in Raising Awareness of Complying with Campus Rules and Regulations at UIN North Sumatra Medan - Toni Nasution (STKIP Taman Siswa Bima, 2023)
This research aims to analyze the role of citizenship education in raising awareness of obeying campus rules and regulations at the North Sumatra State Islamic University, Medan. This type of research uses a qualitative approach with a descriptive analysis study method. Data collection used observation, interviews and document study methods. Next, the data was analyzed using data reduction, data presentation, and drawing conclusions. The results of this research conclude that citizenship education plays an important role in shaping student awareness and behavior regarding campus rules and regulations at UIN North Sumatra Medan. Through citizenship education courses, students gain a deep understanding of the rights and obligations as citizens, the importance of active participation in democratic life, and how to transcend differences to achieve understanding and peace. Furthermore, the role of citizenship education in awareness of obeying campus rules and regulations at UIN North Sumatra is to create students who are disciplined, intelligent and responsible in living campus life. Students become more aware of their rights and obligations as citizens, as well as respecting differences and following applicable rules.